Russia and Spain in the mirror of journalistic discourse: metaphors and stereotypes - M. V. LARIONOVA (Vestnik MGIMO-Universiteta)
В условиях современного информационного общества СМИ играют ведущую роль в формировании и закреплении в сознании национальных стереотипов как особых концептуальных образований, содержащих устойчивые мнения, суждения о какой-либо нации. Газетно-публицистический дискурс, активно тиражируя используемые журналистами этностереотипы, не только отражает специфику национального сознания, но и способствует усилению прагматического воздействия текстов политической коммуникации на существующую в сознании читателей картину мира. В статье на примере сложившихся представлений о России и Испании рассматриваются процессы моделирования с помощью стереотипов и метафор образа одной нации в ментальном пространстве носителей иной лингвокультуры. Marina V. Larionova Russia and Spain in the mirror of journalistic discourse: metaphors and stereotypes In the information-oriented society mass media accomplish a key mission creating and consolidating in human minds national stereotypes defined as specific conceptual formations which contain established opinions, judgements referring to any nation. The journalistic discourse, actively multiplicating ethno stereotypes used by the press, not only reflects specifics of national consciousness, but also promotes pragmatic influence of texts of political communication on the reader's conceptual anticipation of the world. Using the example of traditional stereotypes of Russia and Spain, the article examines the process of modelling by means of stereotypes and conceptual metaphors of the image of one nation in the mentality of the bearers of another national idiomatic culture.